Inquiry Strategy for Basic Legal English Administration Civic Coresspondence as University Learning System - Prehantoro Prehantoro; Wirawan Pamuji (Innovative: Journal Of Social Science Research, 2023)
Civic Administration Learning subjects contains about how students of university understand and comprehend the application for realizing International Administrative Standards about preceding demanding and arguing correspondence in written context by arranging Business reliability in International Context and regulation . Previous methods are merely applied because of meaningful learning or contextualized teaching learning consideration for improvement, in this term, it had better to analyze about administration students with English material in regard for needs an urgency to read a case text for trade proceeding as it requires intensive understanding inferential writing skills to arrange English Letter as an International Correspondence to Explain the meaning of Subject Matters for International Application. By collecting steps of Teaching with Literal Data, Researcher advances arguments with Descriptive Qualitative Explanation to provide Analyzes in order that preceding the result. That in this case, lecturer instructs Students to arrange written letter linked to International Correspondence for Administration Internationally as the subject can infer contextual application in international private administrative material instead of just theory but also english contextual application with inquiry strategy.